Conversor Boost de alto ganho baseado na versão bidirecional da célula de comutação de três estados - Alves, Diego Bruno Saraiva (2014)
This paper presents the study and development of a topology of nonisolated converter operating at high frequency, which is suitable for the integration of battery banks, photovoltaic panels, and a high voltage dc link in a single conversion stage. The topology is based on the bidirectional version of the three-state switching cell and is recommended for battery charging, while a 200V dc link can be obtained in a single conversion stage using photovoltaic (PV) panels. The presented converter is able to supply a 200V dc link using a battery bank and a PV array and, depending on the solar irradiance level, it is also possible to charge the batteries by using a single conversion stage. Moreover, all the switches of the converter are able to operate under zero voltage switching (ZVS) condition over a wide operation range. The experimental results are obtained from a 500W laboratory prototype, which has been developed and tested in three situations: energy flow from the battery bank to the load, energy flow from the PV panel to the load; and energy flow from the panel to the battery bank, achieving the efficiency of 94,18%, 96,09% e 94,67% respectively. The high gain afforded by this topology and the excellent performance obtained in all operations mode, shows as a solution where the requirement of increasing the voltage to 200V or 400V from low input voltage energy sources, typically 12V, 24V or 48V, provided by batteries, solar panels or others sources of energy, for Uninterruptable Power Supply (UPS), or a DC link, for example.